2020
DOI: 10.1136/ijgc-2019-000861
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bloodstream infections in gynecological cancer

Abstract: ObjectiveInfections are a threat to frail patients as they have a higher risk of developing serious complications from bloodstream pathogens. The aim of this study was to determine which factors can predict or diagnose bloodstream infections in patients with an underlying gynecologic malignancy.Materials and MethodsBetween July 2016 and December 2017, 68 patients visiting the emergency room with an underlying gynecologic malignancy were evaluated. Variables concerning underlying disease, invasive procedures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(32 reference statements)
3
2
0
Order By: Relevance
“…This result was consistent with the increase in various hospital-acquired infections in recent years [19,20]. In addition, the risk factors may be related to the risk factors for BSI and (or) hospital-acquired infections reported in many previous studies, such as ICU admission, the older age of hospitalized patients (aging population), prolonged hospital stay, leukocytopenia, acute myeloid leukemia and (or) increased use of invasive procedures including central venous catheters (CVC) [21][22][23]. However, more details of the risk factors require further statistical analysis of the decrease in hospital-acquired BSI in our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…This result was consistent with the increase in various hospital-acquired infections in recent years [19,20]. In addition, the risk factors may be related to the risk factors for BSI and (or) hospital-acquired infections reported in many previous studies, such as ICU admission, the older age of hospitalized patients (aging population), prolonged hospital stay, leukocytopenia, acute myeloid leukemia and (or) increased use of invasive procedures including central venous catheters (CVC) [21][22][23]. However, more details of the risk factors require further statistical analysis of the decrease in hospital-acquired BSI in our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…However, we also found that the composition ratio of hospital acquired BSIs increased significantly annually (from 73.4-76.2%). This result was consistent with the increase in various hospital-acquired infections in recent years [16,17] , and the risk factors may be related to the risk factors for BSIs and (or) hospital-acquired infections reported in many previous studies, such as ICU admission, the older age of hospitalized patients (aging population), prolonged hospital stay, leukocytopenia, acute myeloid leukemia and (or) increased use of invasive procedures including central venous catheters (CVCs) [18][19][20] . However, more details of the risk factors require further statistical analysis of the decrease in hospital-acquired BSIs in our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…Previously it was believed that healthcare associated infections were limited to inpatient hospital settings; however, it has recently been demonstrated that a significant number are also experienced in the outpatient setting 12. Our data confirmed that outpatients experienced healthcare associated infections, particularly those undergoing chemotherapy 13. The Healthcare Associated Infections Prevalence Study Group reported that the most frequent types of healthcare associated infections were respiratory tract infections (21.4% pneumonia and 4.3% other lower respiratory tract infections), urinary tract infections (18.9%), surgical site infections (18.4%), bloodstream infections (10.8%), and gastrointestinal infections (8.9%).…”
Section: Discussionsupporting
confidence: 84%